PERAN BPD DALAM PROSES PENYUSUNAN PERATURAN DESA (Studi Di Desa Jembayan Tengah Kecamatan Loa Kulu Kabupaten Kutai Kartanegara Berdasarkan Undang-Undang Nomor 6 Tahun 2014) - Musriadi Musriadi (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2018)
This study aims to determine the position of village regulations in the middle jembayan village, describe the process of making village regulations, making planning processes, and solutions in the process of making village regulations in Jembayan Tengah Loa Kulu District, Kutai Kartanegara Regency based on Law No. 6 of 2014.This research is a qualitative study, with the subject of research being the village and community apparatus that included the village head, the Village Secretary, the Chairman of the BPD, the Chairperson of the RT, and the community of Central Jembayan Village, Loa Kulu District, Kutai Kartanegara Regency. Data collection techniques used in this study were observation, interviews and documentation. This study uses two types of triangulation, namely triangulation of the first data source and triangulation of techniques or methods of data collection.Based on the results of the analysis, the following are concluded: 1) The position of village regulations in the Middle Jembayan Village, Loa Kulu District, Kutai Kartanegara Regency. The existing village regulation is a statutory regulation stipulated by the village head after it has been approved and approved with the Village Consultative Body. Village regulations are part of the regional regulations made by the Village Consultative Body together with the village head where the procedures for their formation are regulated by the designated Regency / City Regional Regulations. 2) Village regulations made in Central Jembayan Village, Loa Kulu Subdistrict, Kutai Kartanegara Regency, in accordance with Government Regulation Number 72 of 2005 concerning villages included in articles 55, 56, 57 and 58, 3) in Jembayan Tengah Village, Loa Kulu District Kutai Kartanegara Regency is: a) Initially the enactment of Government Regulation Number 72 of 2005 concerning Villages that was not immediately followed by the elaboration of regulations issued by the Government Regulations, b) Performance of members of Jembayan Tengah Village BPD Loa Kulu District, Kutai Kartanegara Regency, maximal c) Technical implementation the field still exists which cannot be done with extortion problems (liars levies) given to the community every year. 4) Efforts made by the village government and BPD of Jembayan Tengah Village, Loa Kulu Subdistrict, Kutai Kartanegara Regency to complete preparations that appear in the process of making Village Regulations include: a) The BPD meets once every Monday night to arouse public awareness of the results village regulations. Keywords: Process, Village Regulation, Law No.6 ofÂ  2014